Dubliners in Brazilian and European Portuguese: The Question of Title Translation in “The Dead” - Amaral, Vitor Alevato do (ABEI Journal, 2012)
Dubliners (1914), by James Joyce, has had four full translations intoPortuguese: two in Brazil and two in Portugal. Translations of individual short stories have also been published in collections and magazines. The aim of this article is to discuss the translation of the title of the last and longest short story in Dubliners – “The Dead” – into Brazilian and European Portuguese. The form of the title in English allows a double understanding, that is, as referring to one dead person or to dead people. However, this ambiguity, able to influence the reading of the short story as a whole, is not present in the Portuguese language translations of the title.